Effect of Promotion, Quality of Service and Price on Competitiveness With Brand Image as an Intervening Variable at Ibu Suparni Boutique - Octa Nilam Lukkita Aga (Dinasti Publisher, 2023)
The Influence of Product Quality, Service Quality and Price to Competitiveness with Citra Merek as Intervening VariaBle (Case Study on Suparni Boutique Boutique). This study aims to determine (1) the effect of Product Quality on Competitiveness on Suparni Butik (2) the influence of Service Quality on Competitiveness in Suparni Butik (3) Price Influence on Competitiveness in Suparni Boutique Boutique (4) Product Quality Influence to Citra Merek at Butik IBu Suparni (5) the influence of Service Quality to Citra Merek on Suparni Butik (6) Price Influence on Citra Merek on Suparni Boutique (7) Citra Merek influence to Competitiveness on Suparni Boutique Boutique. This research uses saturated sampling technique. The population of this research is all customer of Mrs. Suparni which amounted to 210 people. This research method uses quantitative research method with LISREL computer program and Structural Equation Modeling (SEM).The result of the research shows that there is a significant influence of Product Quality on Competitiveness in Suparni Boutique Boutique with the value of T Statistics 5,46 ? 1.96. There is a significant influence of Service Quality on Competitiveness at Suparni Boutique Boutique with the value of T Statistics is 6.19 ? 1.96. There is a significant influence on the Competitiveness of Competitiveness in Suparni's Boutique Boutique with the value of T Statistics is 8.03 ? 1.96. There is no significant effect of Product Quality on Citra Merek on Suparni Boutique Bout with T Statistics is 1.83 ? 1.96. There is no significant effect of Service Quality on Citra Merek on Suparni Boutique with T Statistics is 1.56 ? 1.96. There is no significant effect on Citra Merek Prices on Suparni Boutique Boutiques with T Statistics Being 0.54 ? 1.96. There is no significant effect of Citra Merek on Competitiveness in Suparni's Boutique Boutique with the value of T Statistics is 0.53 ? 1.96.